The Influence of Health Promotion Interventions on the Knowledge and Attitudes of Islamic Students Regarding Clean and Healthy Living Behavior at Islamic Boarding Schools in Batang Hari Regency - Puspita Sari; M. Ridwan; Silvia Mawarti Perdana (Pusat Riset dan Inovasi Nasional, 2023)
Islamic boarding schools are one of the educational institutions in Indonesia. Students at Islamic boarding schools gain knowledge from teachers, kyai or ustadz. The increasing number of students in Islamic boarding schools has created habits such as eating together on one tray, not washing hands with soap before eating, sharing toiletries, and even sharing clothes. This bad habit causes an increase in the number of students suffering from illnesses such as acute respiratory infection, diarrhea, typhus and scabies. Clean and healthy living behavior in Islamic boarding schools is a collection of behaviors that are practiced on the basis of awareness as a result of learning, which makes the Islamic boarding school community independently able to prevent disease, improve their health, and play an active role in creating a healthy environment. This research aims to determine the effect of peer education methods on Clean and Healthy Living Behavior of Santri in Islamic Boarding Schools: Study on students of Irsyadul 'Ibad Islamic Boarding School, Batanghari Regency.This research is a quasi-experimental design research with a two-group pre test-post test control group design. The sample size is 84 respondents divided into 2 groups, namely the Peer Education experimental group with 42 respondents and the control group with 42 respondents. Each group lives in a different dormitory. The results of the bivariate analysis test with the Wilcoxon T-Test showed that the intervention group (peer educators) Knowledge p= 0.006, attitude p= 0.003 and the control group knowledge p= 0.000, attitude=0.009. So it can be statistically concluded that the peer education method influences the knowledge and attitudes of students regarding clean and healthy living behavior in the Batanghari Regency Islamic Boarding School. It is hoped that Islamic boarding schools can give more attention to students about the importance of the PHBS program in Islamic boarding schools. Keywords: , , ,